A phase 1 randomized safety, reactogenicity, and immunogenicity study of Typhax: A novel protein capsular matrix vaccine candidate for the prevention of typhoid fever. - Robert T Cartee; Ann Thanawastien; Thomas J Griffin Iv; John J Mekalanos; Stephan Bart; Kevin P Killeen (PLoS Neglected Tropical Diseases)
Background Typhoid fever remains a significant cause of morbidity and mortality in developing countries especially in children ≤5 years old. Although the widely available unconjugated Vi polysaccharide vaccines are efficacious, they confer limited, short-term protection and are not approved for young children or infants. Vi conjugate vaccines, however, are now licensed in several typhoid endemic countries for use in children >6 months of age. As an alternative to conjugate vaccines, Matrivax has applied its novel 'virtual conjugation' Protein Capsular Matrix Vaccine (PCMV) technology to manufacture Typhax, which is composed of Vi polysaccharide entrapped in a cross-linked CRM197 matrix. Methodology A randomized, double-blinded, dose escalating Phase 1 study was performed to compare the safety and immunogenicity of three dose levels of aluminum phosphate adjuvanted Typhax (0.5, 2.5, or 10 μg of Vi antigen) to the FDA licensed vaccine, Typhim Vi, and placebo. Groups of 15 healthy adult subjects aged 18 to 55 years were randomized and received Typhax, Typhim Vi, or placebo at a ratio of 9:3:3. Typhax and placebo were administered in a two-dose regimen (Days 0 and 28) while Typhim Vi was administered as a single-dose on Day 0 with a placebo administered on Day 28. All doses were administered as a 0.5 mL intramuscular (IM) injection in a blinded fashion. The anti-Vi IgG antibody response was determined preimmunization (Day 0) and on Days 14, 28, 42, and 180 by ELISA. Seroconversion was defined as a titer 4-fold or greater above baseline. Principal findings All Typhax vaccine regimens were well tolerated and adverse events were low in number and primarily characterized as mild in intensity and similar in incidence across the treatment groups. Reactogenicity, primarily pain and tenderness at the injection site, was observed in both the Typhax and Typhim Vi treatment groups; a modest increase in incidence was observed with increasing Typhax doses. Following one dose of Typhax, seroconversion rates at day 28 were 12.5%, 77.8%, 66.7% at the 0.5, 2.5, and 10 μg dose levels, respectively, compared to 55.6% and 0% in the Typhim Vi and placebo groups, respectively. A second dose of Typhax on Day 28 did not elicit a significant increase in GMT or seroconversion at Day 42 or Day 180 at any dose level. Conclusions Collectively, the results from this randomized phase 1 clinical trial indicate that Typhax is safe, well tolerated, and immunogenic. After a single dose, Typhax at the 2.5 and 10 μg dose levels elicited comparable anti-Vi IgG titers and seroconversion rates as a single dose of Typhim Vi (25 μg dose). A second dose of Typhax at Day 28 did not elicit a booster response. Trial registration ClinicalTrials.gov NCT03926455.